2022
DOI: 10.3389/fimmu.2022.865395
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MIF and IL-10 as Molecular Yin-Yang in the Modulation of the Host Immune Microenvironment During Infections: African Trypanosome Infections as a Paradigm

Abstract: African trypanosomes are extracellular flagellated unicellular protozoan parasites transmitted by tsetse flies and causing Sleeping Sickness disease in humans and Nagana disease in cattle and other livestock. These diseases are usually characterized by the development of a fatal chronic inflammatory disease if left untreated. During African trypanosome infection and many other infectious diseases, the immune response is mediating a see-saw balance between effective/protective immunity and excessive infection-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 256 publications
(332 reference statements)
0
1
0
Order By: Relevance
“…Several studies have repeatedly shown that IFN-γ is essential for parasite clearance and protective efficacy [ 53 , 55 ]. In malaria infection, IL-10 is a potent suppressor of several pro-inflammatory cytokines such as IFN-γ, making it detrimental to the cell-mediated immune response [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have repeatedly shown that IFN-γ is essential for parasite clearance and protective efficacy [ 53 , 55 ]. In malaria infection, IL-10 is a potent suppressor of several pro-inflammatory cytokines such as IFN-γ, making it detrimental to the cell-mediated immune response [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%